Molecular Subtypes of Oral Squamous Cell Carcinoma Based on Immunosuppression Genes Using a Deep Learning Approach - Li, Simin; Mai, Zhaoyi; Gu, Wenli; Ogbuehi, Anthony Chukwunonso; Acharya, Aneesha; Pelekos, George; Ning, Wanchen; Liu, Xiangqiong; Deng, Yupei; Li, Hanluo; Lethaus, Bernd; Savkovic, Vuk; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: The mechanisms through which immunosuppressed patients bear increased risk and worse survival in oral squamous cell carcinoma (OSCC) are unclear. Here, we used deep learning to investigate the genetic mechanisms underlying immunosuppression in the survival of OSCC patients, especially from the aspect of various survival-related subtypes. Materials and Methods: OSCC samples’ data was obtained from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), and OSCC-related genetic datasets with survival data in National Center for Biotechnology Information (NCBI). Immunosuppression genes (ISGs) were obtained from the HisgAtlas and DisGeNET databases. Survival analyses were performed to identify the ISGs with significant prognostic values in OSCC. A deep learning (DL)-based model was established for robustly differentiating the survival subpopulations of OSCC samples. In order to understand the characteristics of the different survival-risk subtypes of OSCC samples, differential expression analysis and functional enrichment analysis were performed. Results: 317 OSCC samples were divided into one inferring cohort (TCGA) and four confirmation cohorts (ICGC set, GSE41613, GSE42743, and GSE75538). 11 ISGs (i.e., BGLAP, CALCA, CTLA4, CXCL8, FGFR3, HPRT1, IL22, ORMDL3, TLR3, SPHK1, and INHBB) showed prognostic value in OSCC. The DL-based model provided two optimal subgroups of TCGA-OSCC samples with significant differences (P=4.91E-22) and good model fitness [concordance index (C-index) =0.77]. The DL model was validated by using four external confirmation cohorts: ICGC cohort (n=40, C-index=0.39), GSE41613 dataset (n=97, C-index=0.86), GSE42743 dataset (n=71, C-index=0.87), GSE75538 dataset (n=14, C-index=0.48). Importantly, subtype Sub1 demonstrated a lower probability of survival and thus a more aggressive nature compared with subtype Sub2. ISGs in subtype Sub1 were enriched in the tumor-infiltrating immune cells-related pathways and cancer progression-related pathways, while those in subtype Sub2 were enriched in the metabolism-related pathways. Conclusion: The two survival subtypes of OSCC identified by deep learning can benefit clinical practitioners to divide immunocompromised patients with oral cancer into two subpopulations and give them target drugs, and thus might be helpful for improving the survival of these patients and provide novel therapeutic strategies in the precision medicine area.